Analysis of the coupling coordinated development and evolutionary trend of digital economy and ecological environment - Fu, Lianyan; Liu, Bo; Zhu, Zhichuan; Cao, Jianhong; Sun, Congting; Yu, Zhuoxi (Frontiers in Environmental Science, 2022)
In the context of rapid development of the digital economy and growing ecological environment problems, it is of great practical importance to clarify the coordinated development of digital economy and ecological environment. In this paper, China is selected as the research region, and the evaluation system is established with the relevant indicators of its digital economy and ecological environment from 2011-2019. The level of coordinated development between the two is calculated with the help of entropy method and coupling coordinated development model. The spatial and temporal evolution trends of their coordinated development levels and regional differences were further explored through kernel density analysis and Dagum Gini coefficient decomposition. The results shows that (1) both the level of digital economy, the level of ecological environment and the level of coupling coordination between the two have increased. (2) By region, the level of coordinated development shows regional heterogeneity, with the highest in the eastern region, followed by the central region, and the lowest in the western region. (3) The inter-regional differences show a fluctuating downward trend, and the differences between the east and west are the largest, followed by the east-central region, and then the central-western region. The analysis of the above methods provides a basis for understanding the spatial and temporal evolution characteristics of the coordinated development of China's digital economy and ecological environment, and also provides relevant policy recommendations for promoting coordinated and sustainable development among regions.